CYBER PESANTREN SEBAGAI PROFIL GAGASAN PESANTREN DI ERA MILENIAL - Ach Rofiq (STIT AL-ISHLAH BONDOWOSO, 2018)
Pesantren (Islamic Boarding School) as a Islamic education system media has get improvement and development quickly in Globalisation era. Pesantren not only as meaning of Islamic education institution consist of kyai (muslim scholar), santri (student of Islamic Boarding School), Mosque, Boarding School, and classical teks book, but it has evolute in to various designs functionally. Globalization era gives it positif effect to enlarge the meaning and function of Boarding School exactly. Technologys product like computer, internet, dan another gives many facilities for developing pesantren mission as religion and morality entrenchement. In this article, the writer use phenomenology theories of Edmund Husserel to get right conclution of phenomenom that is in social media as product of thecnology like facebook, messanger, black berry messanger, what up, tweeter act. There was apllied any kinad of Islamic discursus and doctrin explained like reading Islamic books, good advices, halaqah, speech, Islamic therapies and ect. This phenomenom writer called it by Cyber Pesantren cause, substansialy has same function and vision with convensional Islamic Boarding School as we knew nowadays. Eventhough, there were any distinguish between Pesantren in fact and Cyber Pesantren. But, it will be new step for Islamic discursus to enlarge and showing what is pesantren and what are in it easily.